Between Hierarchy and Individuality: the Andean Community of Nations’ historical rationalities (Tema Central) - Garcés Velástegui, Pablo Fernando (Quito, EC: Universidad Andina Simón Bolívar / Corporación Editora Nacional, 2020)
In its 50 years, CAN has faced important challenges, some have even threatened its existence. Nevertheless, the fact that it has survived is a testament to its success. On the face of greatly changing political and economic environments, the continuity of its work can be explained by its ability to adapt to the situation. In this half of century, the mechanism has undergone more than one existential crisis and it has tackled each with important self-reforms. These modifications have sought to renew its relevancy. In order to make sense of this adaptation, this article uses grid-group cultural theory to identify the main rationalities or worldviews that have driven this regional integration process. The analysis shows that CAN has mainly moved between hierarchical and individualistic ways of life, and points to some implications for its near future.
En sus 50 años de vida, la CAN ha enfrentado importantes desafíos, algunos de los cuales incluso han amenazado su existencia. Sin embargo, el hecho de que haya sobrevivido es un testimonio de su éxito. Frente a entornos políticos y económicos muy cambiantes, la continuidad de su trabajo se explica por su capacidad de adaptación a las circunstancias. En este medio centenar de años, el organismo ha atravesado más de una crisis existencial y las ha abordado con importantes autorreformas. Estas modificaciones han buscado renovar su relevancia. Con el fin de darle sentido a esta adaptación, este artículo utiliza la teoría cultural de cuadrícula y grupo (grid-group cultural theory) para identificar las principales racionalidades o visiones del mundo que han impulsado este proceso de integración regional. El análisis muestra que CAN se ha movido principalmente entre formas de vida jerárquicas e individualistas y señala algunas implicaciones para su futuro cercano.
Keywords: COMUNIDAD ANDINA; INTEGRACIÓN SUBREGIONAL ANDINA; INTEGRACIÓN LATINOAMERICANA; PACTO ANDINO; REGIONAL INTEGRATION; ANDEAN COMMUNITY